Application of Root Conflict Analysis (RCA+) to Identify Contradiction in Manufacturing Process - Faishal Arham Pratikno; Muhamad Imron Zamzani; Noni Oktiana Setiowati (Universitas Islam Raden Rahmat, Malang, 2023)
The presence of defects is a sign that the level of quality is not good enough. In this paper, we will discuss root cause analysis in the manufacturing process. In addition to analyzing the root of the problem, there are usually conditions called contradictions. Contradiction means a condition in which positive and negative effect simultaneously occur at the same time. Therefore, the Root Conflict Analysis (RCA+) has been adopted to find the root cause of the problem and at the same time identify the contradictions. Implementation of this method is carried out on the drilling process of composite fiber-reinforced plastic (CFRP). Based on the results, it was found that there are 3 causes of problems in the drilling process, high cutting speed, high feed rate and large point angle. As well as found several contradictions, regarding drilling productivity, tool temperature, thrust force during the process and drill burr.